Reconciling scientific reality with realpolitik: moving beyond carbon pricing to TEQs – an integrated, economy-wide emissions cap. Issue 4 (4th July 2014) - Chamberlin, Shaun; Maxey, Larch; Hurth, Victoria
Abstract : This article considers why price-based frameworks may be inherently unsuitable for delivering unprecedented global emissions reductions while retaining the necessary public and political support, and argues that it is time to instead draw on quantity-based mechanisms such as TEQs (tradable energy quotas). TEQs is a climate policy framework combining a hard cap on emissions with the use of market mechanisms to distribute quotas beneath that cap. The significant international research into TEQs is summarized, including a 2008 UK government feasibility study, which concluded that the scheme was "ahead of its time." TEQs would cover all sectors within a national economy, including households, and findings suggest it could act as a catalyst for the socio-technical transitions required to maximize wellbeing under a tightening cap, while generating national common purpose toward innovative energy demand reductions. Finally, there are reflections on the role that the carbon management community can play in further developing TEQs and reducing the rift between what climate science calls for and what politics is delivering.